Impact of melatonin on periodontal ligament fibroblasts during mechanical strain. (9th April 2022) - Schröder, Agnes; Alefeld, Annika; Forneck, Anne; Spanier, Gerrit; Deschner, James; Proff, Peter; Kirschneck, Christian
Summary: Background: The endogenous hormone melatonin regulates the circadian rhythm and impacts on bone metabolism. As patient compliance to wear removable orthodontic appliances is generally higher at night, when melatonin release is increased, a boosting effect on tooth movement would be favourable for therapy, whereas an inhibiting effect would indicate daytime wear to be more therapy-effective. We hypothesize that melatonin has either a stimulating or impeding effect on the expression profile of periodontal ligament fibroblasts (PDLF) during simulated orthodontic compressive and tensile strain, which would suggest either an accelerating or inhibiting impact on orthodontic tooth movement in vivo. Methods: PDLF were preincubated with melatonin for 24 h and then subjected to tensile or compressive strain to mimic tension and pressure sides in PDL. In addition, the selective melatonin MTNR1B-receptor antagonist 4P-PDOT was used. We investigated melatonin effects on collagen synthesis, expression of inflammatory and bone-remodelling genes/proteins by quantitative real-time polymerase chain reaction, enzyme-linked immunosorbent assays, and total collagen assays. PDLF-induced osteoclastogenesis was analysed in a coculture model by tartrate-resistant acid phosphatise (TRAP) staining. Results: Expression of melatonin receptors in PDLF was not affected by compressive strain. Melatonin increased expression of inflammatory factors and elevated collagen synthesis during mechanical strain. Melatonin showed no effects on OPG or RANKL expression without mechanical strain, but increased RANKL gene expression during compression. Conclusions: Expression of melatonin receptors by PDLF enable them to detect fluctuating melatonin concentrations in the periodontal ligament. Melatonin increased collagen synthesis and expression of inflammatory mediators, but had no effect on genes involved in bone remodelling. Therefore, we suggest that melatonin has no accelerating effect on PDLF-induced osteoclastogenesis.